Molecular cytogenetic mapping of Secale strictum introgressions in a perennial tetraploid rye and its diploid progenitor - Ahmed Ali Hamad; Diána Makai; László Sági; Ákos Tarnawa; Adél Sepsi; Dávid Polgári (PLoS ONE, 2026)
Perennial rye offers a means to reduce soil disturbance in water-limited cropping systems; however, the use of interspecific germplasm is often constrained by variable fertility and structurally heterogeneous genomes that are difficult to monitor during selection. Here, we selected a new perennial rye line, ‘Keleti1’, from a Secale cereale × S. strictum hybrid population and generated a tetraploid derivative, ‘Keleti1T’, by colchicine-induced genome duplication. Comparative phenotyping of matched diploid and tetraploid plants showed that genome duplication was associated with reduced plant height, increased thousand-grain weight and fertile tiller number per plant. In contrast, per-spike reproductive performance and seed number per plant exhibited substantial inter-individual variation in tetraploids. Flow cytometry and cytological analyses were used to confirm tetraploid status prior to molecular cytogenetic characterisation. To enable chromosome-level tracing of parental contributions, we applied fluorescence in situ hybridisation using the subtelomeric repeat pSc119.2 and 5S rDNA. These markers revealed polymorphisms on chromosomes 1R and 6R, as well as on 3RL, 4RL, 7RL and 5RS, allowing S. strictum chromatin segments to be distinguished in both diploid and tetraploid backgrounds. Heteromorphic chromosome pairs were detected in all plants analysed, consistent with the outcrossing nature of rye, and non-canonical hybridisation patterns indicated frequent structural rearrangements. Together, these results provide cytogenetic markers for monitoring introgression and document how genome duplication alters agronomic and reproductive traits in a perennial interspecific rye derivative.